Combination of Side-Bending and Traction Radiographs Do Not Influence Selection of Fusion Levels Compared to Either One Alone in Adolescent Idiopathic Scoliosis. Issue 4 (May 2023) - Arima, Hideyuki; Dimar, John R.; Glassman, Steven D; Gum, Jeffrey L.; Carreon, Leah Y.
Study Design: A retrospective study. Objectives: Curve flexibility in patients with adolescent idiopathic scoliosis (AIS) can be evaluated using different techniques. This study aimed to determine whether the combination of side-bending (SB) and traction (TX) radiographs influences preoperative planning for AIS than either radiograph alone. Methods: Thirty-two spine surgeons were asked to review 30 AIS Lenke type 1 cases and select an upper instrumented vertebra (UIV) and lower instrumented vertebra (LIV) for the posterior spinal instrumentation of each case. Each rater reviewed the cases 3 times in each round. The raters were provided with the full-length posteroanterior (PA) and lateral standing and SB radiographs for round 1; PA, lateral, and TX radiographs for round 2; and PA, lateral, SB, and TX radiographs for round 3. Intra- and inter-rater reliabilities were evaluated using Kappa statistics. Results: The intra-rater reliability for UIV and LIV was 0.657 and 0.612 between rounds 1 and 2, 0.634 and 0.692 between rounds 1 and 3, and 0.659 and 0.638 between rounds 2 and 3, respectively, which indicated substantial agreement between rounds. The inter-rater kappa reliabilities for UIV and LIV selection were 0.103 and 0.412 for round 1, 0.121 and 0.380 for round 2, and 0.125 and 0.368 for round 3, indicating slight to moderate agreement between raters. Conclusions: Whether raters used either SB or TX radiography, or both in addition to PA and lateral standing radiographs, did not influence the decision making for UIV or LIV of AIS Lenke type 1 surgery.